The Substitution of Fresh Moringa Leaves and Moringa Leaves Powder on Organoleptic and Proximate Characteristics of Pudding - Mia Srimiati; Lina Agestika (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2022)
Background: Moringa Oleifera leaves